2019
DOI: 10.1530/joe-18-0533
|View full text |Cite
|
Sign up to set email alerts
|

miR-505-3p is a repressor of puberty onset in female mice

Abstract: Puberty onset is a complex trait regulated by multiple genetic and environmental factors. In this study, we narrowed a puberty-related QTL region down to a 1.7 Mb region on chromosome X in female mice and inferred miR-505-3p as the functional gene. We conducted ectopic expression of miR-505-3p in the hypothalamus of prepubertal female mice through lentivirus-mediated orthotopic injection. The impact of miR-505-3p on female puberty was evaluated by the measurement of pubertal/reproduction events and histologica… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…The up-regulation of miR-505-3p in the group of poor oocyte quality is possibly related to infertility. Its over-expression in mice was associated with delayed ovary maturation and lower fertility [ 44 ]. However, Barragán and colleagues, by examining a total of 36 in vivo matured MII oocytes collected from 30 healthy women recruited for oocyte donation, found that five miRNAs such as hsa-miR-220b, miR-4262 and miR-1260a were increased in the older group (age 32 ± 2 years and high antral follicular count approx.…”
Section: Resultsmentioning
confidence: 99%
“…The up-regulation of miR-505-3p in the group of poor oocyte quality is possibly related to infertility. Its over-expression in mice was associated with delayed ovary maturation and lower fertility [ 44 ]. However, Barragán and colleagues, by examining a total of 36 in vivo matured MII oocytes collected from 30 healthy women recruited for oocyte donation, found that five miRNAs such as hsa-miR-220b, miR-4262 and miR-1260a were increased in the older group (age 32 ± 2 years and high antral follicular count approx.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that miRNA is involved in SRSF1 regulation. For example, miR-505-3p targets SRSF1 to inhibit the expression of puberty-related genes, thus regulating sexual maturity [26]; also, both miR-28 and miR-505 target SRSF1 to control mouse embryonic fibroblasts (MEF) proliferation and survival [27]. Additionally, SRSF1 was reported to bind to circRNA [28] and lncRNA [29], as RNA-binding proteins (RBPs) in glioma cells and trophoblast cells, respectively, to regulate the cell proliferation process.…”
Section: Introductionmentioning
confidence: 99%